PURSUIT OF THE PRODUCTIVE WORKER: ASSESSING THE DIRECT AND INDIRECT EFFECTS OF ORGANISATIONAL TRAINING AND GENDER - Raja Nuratiqah Raja Azlan,; Nurul Hidayana Mohd Noor, (Journal of Human Capital Development (JHCD), 2025)
ABSTRACT Upskilling and reskilling of the workforce are necessary to ensure that staff can deal with the rapidly changing needs of the labour market. This training is suitable for managers, supervisors, and staff at all levels of the organization who want to improve employee performance and overall organizational productivity. This study aims to determine the moderating influence of gender, which subsequently affects the relationships between perceived availability of training, perceived co-worker training support, perceived supervisor training support, and employee productivity. This study was conducted at Modle Solutions PLT and involved 132 randomly selected respondents. A questionnaire was used as a research instrument. The data obtained was analysed using descriptive statistics and hierarchical linear regression. This study's results show a significant relationship between perceived availability of training, perceived co-worker support for training, perceived supervisor support for training, and employee productivity. The results also showed that gender moderates the relationship between perceived co-worker support for training, perceived supervisor support for training, and employee productivity. This study is expected to be an effective platform for strengthening strategies in the holistic development of human capital. In addition, it can help the related parties ensure that the people work in an encouraging environment. Keywords: organizational training; employee productivity; gender; moderating effect